Model development of counseling competency dealing with gay and lesbian client: Malaysia perspective - Amat, Salleh; Jamal, SitiHajar; Mahmud, Mohd Izwan; Fuad Mohd Karim, Dharatun Nissa (School of Education, South Carolina State University, 2021)
This study has developed a framework model in the practice of gay and lesbian counseling in Malaysia based on the findings of a research related to counseling competencies in managing gay and lesbian clients. The study also use qualitative design involving semi-structured in depth interviews. The purposive sampling is used to interview fifteen counselors which have been identified by researcher to have information regarding the management of counseling session for gay and lesbian clients. Fifteen counselors have been chosen to complete the research based on two selection of sampling criteria in this study that are registered counselors and counselors who have experiences in handling gay and lesbian clients. The findings of the study provided view into the need for the development of gay and lesbian counseling models in providing enlightenment and guidance to counselors on the procedures and processes for managing gay and lesbian cases. The development of this model is also based on the conceptual framework that has been developed by the researcher. Researchers used Iceberg's competency model to look at skills, knowledge and attitudes. In this theory, it has been discussed that knowledge and skills are elements of competency that are easy to develop, while the concepts of self, nature, motive and social role are things hidden within one's personality and are difficult to develop. Therefore, the researcher has chosen a social role that advises the counselor in providing awareness to clients to gain common sense during the session. Elements of counselor competence include knowledge, skills, attitudes, determination and values to enhance counselors' ability to deal with gay and lesbian clients. In summary, this model of gay and lesbian counseling can contribute to professional counseling institution and can assist educators in the field of counseling so that trained counselors are more competent in dealing with gay and lesbian issues.